Inflammatory Bowel Disease and Statins - V. V. Genkel; I. I. Shaposhnik (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. To present up-to-date information on the possibility of using statins in patients with inflammatory bowel disease (IBD).Highlights. Statins exhibit immunomodulatory effects, which are of particular importance with regard to IBD treatment. Experimental studies, which demonstrate positive effects of statins on various characteristics of the IBD course, were reviewed. The use of statins led to a decrease in the histological activity in models with DSS- and TNBSinduced colitis. Pravastatin was shown to decrease both the epithelial permeability and crypts. Simvastatin changed the composition of the intestinal microflora, which had a potential anti-inflammatory effect. According to the results of clinical studies, atorvastatin administration to IBD patients resulted in a statistically significant decrease in the serum markers of inflammation and the activity index of ulcerative colitis. Retrospective clinical studies demonstrated different effects of statins on the risk of IBD.Conclusions. A number of potentially protective effects of statins on inflammatory bowel diseases have been identified. However, well-planned randomised clinical trials are needed to evaluate the effects of statins in IBD.